Pt, Re and Pt–Re incorporation in sulfated zirconia as catalysts for n-pentane isomerization - A.K. Aboul-Gheit; F.K. Gad; G.M. Abdel-Aleem; D.S. El-Desouki; S.M. Abdel-Hamid; S.A. Ghoneim; A.H. Ibrahim (Egyptian Journal of Petroleum)
Two groups of modified Sulfated Zirconia (SZ) catalysts were prepared by the sol–gel method. The first group was modified by four different concentrations of Pt metal (0.15, 0.30, 0.45 and 0.60 wt%), whereas the second group contained Pt–Re combinations on SZ. All the prepared catalysts were characterized by XRD, TPR, TEM, TGA, IR spectroscopy as well as surface properties using the BET method. The catalytic activity of the catalysts was examined for the hydroisomerization of n-pentane to iso-pentane. The catalytic activity was found to increase with increasing Pt concentration in the monometallic catalysts. The combination of Re ion with Pt on SZ results in significant changes in the characters and activities of the catalysts. The 0.45 wt%Pt + 0.15 wt%Re/SZ catalyst exhibited the highest selective compared to other metal ratios investigated.